Sistemas de numeração posicionais e não posicionais - Santos, Anderson Flávio dos [UNESP] (2014)
The necessity of using numbers is a historical process and essencial to the organization of human life, although it is an abstract concept. Since Early Middle Ages, when human beings still lived in caves, the need for counting had always existed because fishes, herds, plantations had to be counted. Even nowadays the most diverse and developed technologies use numbers like the computacional binary numeral system. The aim of this paper is to explain how numeral systems have been used throughout history, their necessity, calculation and aplication. Besides this, comparisons between the most used systems will be presented, distinguishing positional and non positional numeral systems. It is also intended to suggest reflection about this systems models advantages and disadvantages. Also pratical activities applied to children in fourth and fifth grades of primary and secondary school results will be present. The purpose is showing how children understand numbers positioning of decimal number system in order to highlight that the memorizing habit prevails performing basic operations of this system due to the fact people do not understand it. This fact makes the students of Brazilian schools do not have basic math skills, and, consequently, the country does not present desirable results on international assessments. In summary, the main purpose of this paper is being an opportunity for reflection presenting math history, demonstrating numbering systems simple concepts and showing that someone really learns to manipulates numbers when they are really understood